PROSES PEMBUATAN DJEMBE OLEH PURWANTO - Muhammad Afandi Setiawan; Sigit Astono (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2021)
The research entitled "The Process of Making Djembe by Purwanto" is qualitative. The research subject is focused on making a musical instrument which is carried out in Purwanto, one of the craftsmen in the city of Surakarta. Djembe becomes the object of research because the phenomenon that occurs in this musical instrument is experiencing extraordinary development in Surakarta. This development cannot be separated from the services and talents of Purwanto, which are recognized by various music artists, especially djembe users. Besides, the djembe made by Purwanto is of high quality in terms of ingredients and products.This study uses an ethnographic approach. Researchers go directly to follow the process carried out by the resource person to obtain data and information about the process of making a djembe instrument. To answer this research problem, the concept of Mantle Hood organology is used, which discusses the science of musical instruments in a broad sense that is limited to history and physical description and the development of processes and the role of musical instruments in one ensemble.The results of data analysis and facts collected through interviews, observations, and literature studies are the process of making developmental djembe on equipment. This development is found in:Choosing a good wood material, namely mahogany.Choosing a good leather material, namely cow and goatskin.The manufacturing process using machine technology.Good quality is djembe which can produce bass, tone, and slap sound well.